Carmen Concilio, Daniela Fargione. Trees in Literatures and the Arts - Boraso, Silvia (Il Tolomeo, 2021)
Review of Concilio, C.; Fargione, D. (eds) (2021). Trees in Literatures and the Arts. HumanArboreal Perspectives in the Anthropocene. Lanham: Lexington Books, 321 pp.